Biografi ulama Malaysia : Yusoff Zaky YacobYusoff Zaky Yacob : dian yang tak kunjung padam - Asmadi Yakob; Mustaffa Abdullah (Biografi ulama Malaysia, 2011)
Biography of Yusoff Zaky Yacob, a Malaysian ulama and Muslim scholar from Kelantan